Contributing factors of customer dissatisfaction with service quality at post office in Wilayah Persekutuan / Nor Marina Mohtar - Mohtar, Nor Marina (Faculty of Business and Management, 2007)
This research is about contributing factors of customer dissatisfaction at Post office in Wilayah Persekutuan. There are many factors that contribute to the dissatisfaction with the service at the Post Office. This study, thus have the following objectives: